ANCA vasculitis: A manifestation of Post-Covid-19 Syndrome. (2021) - Morris, Desiree; Patel, Kushal; Rahimi, Osman; Sanyurah, Omar; Iardino, Alfredo; Khan, Nazia
Abstract: The SARS-CoV-2 infection has been found to present with different degrees of response and variable levels of inflammation. Patients who have recovered from the initial infection can develop long-term symptomatology. We present a unique case of a middle aged-healthy man who developed complications of ANCA-associated vasculitis after recovering from a mild COVID-19 infection. A previously healthy 53-year-old male presented with hemoptysis and acute renal failure. One month prior, the patient tested positive for COVID-19; not requiring hospitalization. Physical exam findings included bilateral lower extremity petechiae. CT Chest showed bilateral diffuse patchy lung consolidations with cavitary lesions with urinalysis revealing erythrocytes, +1 protein. Hemodialysis and workup for pulmonary-renal syndromes were initiated. Infectious workup results included: negative COVID-19, negative MTB-PCR, respiratory culture revealing yeast. Additional workup revealed; elevated CRP, D-Dimer, and Fibrinogen. Notably, the patient had; decreased C3 and C4 levels; negative Anti-GBM antibody; negative Anti-streptolysin-O; and positive ANCA assay, Proteinase antibody, and mildly positive Myeloperoxidase antibody. Worsening coagulopathy and atrophic kidneys delayed renal biopsy for definitive diagnosis. The patient's respiratory status acutely worsened during hemodialysis with imaging showing markedly increased pulmonary infiltrates. Upon urgent intubation, active frank red bleeding was noted, and the patient sustained 2 cardiac arrests with eventual expiration. Much is to be learned from the Novel SARS-CoV-2 virus and suspected complications. This case highlights a unique complication of COVID-19 leading to a possible AAV and the importance of keeping a broad differential when treating patients who have recovered from the initial infection. Highlights: COVID-19 renal complications. ANCA-associated vasculitis after COVID-19. Acute renal failure after resolution of COVID-19.